Pain, Passion and Faith: Revisiting the Place of Charles Wesley in Early Methodism - Cruickshank, Joanna (Rowman & Littlefield Publishers, 2009)
Pain, Passion and Faith: Revisiting the Place of Charles Wesley in Early Methodism is a significant study of the 18th-century poet and preacher Charles Wesley. Wesley was an influential figure in 18th-century English culture and society; he was co-founder of the Methodist revival movement and one of the most prolific hymn-writers in the English language. His hymns depict the Christian life as characterized by a range of intense emotions, from ecstatic joy to profound suffering. With this book, author Joanna Cruickshank examines the theme of suffering in Charles WesleyOs hymns, to help us understand how early Methodist men and women made sense of the physical, emotional and spiritual pains they experienced. Cruickshank uncovers an area of significant disagreement within the Methodist leadership and illuminates Methodist culture more broadly, shedding light on early Methodist responses to contemporary social issues like charity, slavery, and capital punishment.